2017
DOI: 10.1007/s12035-017-0578-3
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Can Epigenetically Alter the Gene Expression of Neurotrophic Factors in the Murine Brain Cells

Abstract: Glucose is believed to improve the memory in both human and mice, but the detailed insights were mostly elusive. In this study, we focused on two major neurotrophic factors, brain-derived neurotrophic factor (BDNF) and fibroblast growth factor 1 (FGF1), which are believed to be associated with the memory enhancement and assessed their expressional regulation among the murine neuronal and glial cells. Our findings showed that the glucose administration increased phosphorylated Akt, phosphorylated CREB, exon 1- … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…Therefore, the stabilized cerebral energy provision relies on the regular glucose metabolism. As a major energy substrate, glucose is almost fully oxidized in brain, which not only supplies ATP for neuronal and non-neuronal cellular survival, but also can be as precursor for neurotransmitters biosynthesis (Dienel, 2012; Harris et al, 2012; Howarth et al, 2012; Mergenthaler et al, 2013; Hossain et al, 2018). When cerebral ischemia occurs, the provision of glucose is insufficient, which will cause neurons necrosis in ischemic central region within a few minutes and the damage gradually extends to the surrounding zone (Dirnagl et al, 1999; Mergenthaler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the stabilized cerebral energy provision relies on the regular glucose metabolism. As a major energy substrate, glucose is almost fully oxidized in brain, which not only supplies ATP for neuronal and non-neuronal cellular survival, but also can be as precursor for neurotransmitters biosynthesis (Dienel, 2012; Harris et al, 2012; Howarth et al, 2012; Mergenthaler et al, 2013; Hossain et al, 2018). When cerebral ischemia occurs, the provision of glucose is insufficient, which will cause neurons necrosis in ischemic central region within a few minutes and the damage gradually extends to the surrounding zone (Dirnagl et al, 1999; Mergenthaler et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Inconsistent findings regarding the effect of glucose on Bdnf gene expression in microglial cell lines may be explained by the difference in the experimental design between the two studies. In the study by Hossain et al [15], the effect of glucose was examined at lower concentrations (2.5 vs. 7 mmol/l) compared with those in the present study (17.5 vs. 25 mmol/l). MG6 cell line was established from mouse whole brain and immortalized by viral transduction with oncogenes, whereas SIM-A9 is a spontaneously immortalized cell line obtained from mouse cerebral cortex [10,16].…”
Section: Discussionmentioning
confidence: 67%
“…Moreover, 2-DG treatment reduced levels of pan-Bdnf mRNA in primary cultured cells from rat mediobasal hypothalamus [14]. It was also reported that increased glucose concentration enhances pan-Bdnf mRNA expression in neuronal and astrocyte cell lines, but not in microglial MG6 cells [15]. Inconsistent findings regarding the effect of glucose on Bdnf gene expression in microglial cell lines may be explained by the difference in the experimental design between the two studies.…”
Section: Discussionmentioning
confidence: 99%
“…HDACs have been shown to regulate soluble factors in different cell types. In neuronal and glial cells, the release of brain-derived neurotrophic factor (BDNF) and fibroblast growth factor 1 (FGF1) is mediated by HDACs ( Hossain et al, 2018 ), as well as in fibroblasts the production of several proinflammatory cytokines/chemokines ( Li et al, 2011 ), thus contributing to chronic inflammatory processes. Moreover, HDACs modulate IL-4 expression and secretion in mast cells and monocyte-derived DCs (moDCs) ( López-Bravo et al, 2013 ; Nakamaru et al, 2015 ).…”
Section: Discussionmentioning
confidence: 99%